Perioperative, oncologic, and functional outcomes of robot-assisted partial nephrectomy for special types of renal tumors (hilar, endophytic, or cystic): an evidence-based analysis of comparative outcomes - Chen, Xiao-bin; Li, Yu-gen; Wu, Tao; Du, Zhong-bo; Tan, Chun-lin; Zhang, Qiang; Yu, Xiao-dong (Frontiers in Oncology, 2023)
Purpose: This study aims to perform a pooled analysis to compare the outcomes of robot-assisted partial nephrectomy (RAPN) between complex tumors (hilar, endophytic, or cystic) and non-complex tumors (nonhilar, exophytic, or solid) and evaluate the effects of renal tumor complexity on outcomes in patients undergoing RAPN. Methods: Four databases were systematically searched, including Science, PubMed, Web of Science, and Cochrane Library, to identify relevant studies published in English up to December 2022. Review Manager 5.4 was used for statistical analyses and calculations. The study was registered with PROSPERO (Registration number: CRD42023394792). Results: In total, 14 comparative trials, including 3758 patients were enrolled. Compared to non-complex tumors, complex tumors were associated with a significantly longer warm ischemia time (WMD 3.67 min, 95% CI 1.78, 5.57; p = 0.0001), more blood loss (WMD 22.84 mL, 95% CI 2.31, 43.37; p = 0.03), and a higher rate of major complications (OR 2.35, 95% CI 1.50, 3.67; p = 0.0002). However, no statistically significant differences were found between the two groups in operative time, length of stay, transfusion rates, conversion to open nephrectomy and radical nephrectomy rates, estimated glomerular filtration rate (eGFR) decline, intraoperative complication, overall complication, positive surgical margins (PSM), local recurrence, and trifecta achievement. Conclusions: RAPN can be a safe and effective procedure for complex tumors (hilar, endophytic, or cystic) and provides comparable functional and oncologic outcomes to non-complex tumors.